Learning 2.0 in information literacy 0.0 territory: the case of Croatia - Špiranec, Sonja (Array, 2010)
The generation of “learner 2.0” has grown up. It is a generation for whom technology is a way of life, who choose different information paths and who learn in new ways. This is a global phenomenon, and, as our surveys have shown, visible among the Croatian student population as well. In the case of Croatia and many other Central European and South Eastern European countries, it is also a generation who has grown up on Information Literacy 0.0 territory, without a clearly devised strategy or policy that would guarantee or direct information literacy implementations. The panelist will describe the contextual elements of the poor state of information literacy in this European region, and point out how the spread of Web 2.0 has further contributed to the fuzziness of information landscapes for students who are functioning without IL instruction, specifically with regard to the fact that IL has been reconceptualized as “information literacy 2.0”. In conclusion, comments will be made about the effects of these developments on different stakeholders (librarians, educators, students), and what additional steps need to be taken.